The Effectiveness of the Roundtable Cooperative Learning Model to Increase Interest in Learning Mathematics in Class VIII-2 at SMP Negeri 2 Padangsidimpuan - Jefritua Manurung (RADINKA JAYA UTAMA PUBLISHER, 2023)
This research was conducted to find out how the implementation of the Roundtable cooperative learning model is significant to increase interest in learning Mathematics in Kelas VIII-2 in SMP Negeri 2 Padangsidimpuan. The participants of this qualitative research were 28 students and the researcher himself was involved as a participant-observer. This research was conducted in two cycles and data collection did by observation and document analysis. The findings were then analyzed qualitatively by explaining and elaborating according to relevant theories. This study proves that the implementation of the Roundtable cooperative learning model significantly increased interest in learning Mathematics in Kelas VIII-2 in SMP Negeri 2 Padangsidimpuan. The implementation of the cooperative learning model seems to be potential in increasing group working, communication skills, and learning outcomes of the students. However, heterogeneous groups seem to be important in group work to make the learning activities interesting and meaningful for students. Hence, relevant studies still recommended gaining significant and better findings.